Lipreading as a communication strategy to enhance speech recognition in individuals with hearing impairment: a scoping review. - Santana, Rafael S.; Menezes, Edenia C.; Ralin, Vera; Givigi, Sidney; Batorowicz, Beata (Disability & Rehabilitation: Assistive Technology, 2025)
Purpose: This article explores the existing research evidence on the potential effectiveness of lipreading as a communication strategy to enhance speech recognition in individuals with hearing impairment. Methods: A scoping review was conducted, involving a search of six electronic databases (MEDLINE, Embase, Web of Science, Engineering Village, CINAHL, and PsycINFO) for research papers published between January 2013 and June 2023. This study included original research papers with full texts available in English, covering all study designs: qualitative, quantitative, and mixed methods. These studies had to examine lipreading as an approach to enhance speech recognition and involve metrics of word recognition accuracy or speech recognition performance. Results: This review identified a total of 18 articles that met the inclusion criteria. The research evidence is limited to descriptive analysis of lipreading to enhance speech recognition. Most of the studies focused on audiological, computational and hearing-related aspects. The features supporting the effectiveness of lipreading were found to be related to (a) Speaker: The accurate lip movements and the role of facial expressions; (b) Person lipreading: Skills and personal characteristics; (c) Technology to capture and/or support lipreading, and (d) Environmental and contextual factors. Conclusion: Findings of this review indicate that lipreading can be an effective approach to enhancing speech recognition of people with hearing disabilities, giving attention to a combination of the factors related to individuals with hearing impairment, speaker, environment, and technology. Further research is required to investigate interaction among these factors to inform development of efficient lipreading systems. IMPLICATIONS FOR REHABILITATION: This scoping review helps to advance the understanding of how lipreading can enhance speech recognition of people with hearing impairment. The findings of this review indicate a need to include multimodal approaches that integrate both auditory and visual cues to improve speech recognition. There is a need for more research to grow evidence-based practice related to improving speech recognition and communication of people with hearing impairment.